Reference Points, Prospect Theory, and Momentum on the PGA Tour. (June 2016) - Stone, Daniel F.; Arkes, Jeremy
Pope and Schweitzer (2011) study predictions of prospect theory for the reference point of par on the current hole in professional golf. We study prospect-theory predictions of three other plausible reference points: par for recent holes, for the round, and for the tournament. A potentially competing force is momentum in quality of play, that is, the hot or cold hand. While prospect theory predicts negative serial correlation in better (worse)-than-average performance across holes, the hot (cold) hand implies the opposite. We find evidence that, for each of the reference points we study, when scores are better than par, hot-hand effects are dominated by prospect-theory effects. These effects can occur via two mechanisms: greater conservatism or less effort. We find evidence that the former (latter) dominates for scores closer to (further from) the reference point. We also find evidence of prospect theory effects (greater risk seeking) when scores are worse than par for the round in Round 1 and of cold-hand effects for scores worse than par for the tournament in Round 3. The magnitudes of some of the joint effects are comparable to those found by Pope and Schweitzer and other related papers. We conclude by discussing how, rather than compete, prospect-theory and cold-hand forces might also cause one another.